VARICELLA ZOSTER VIRUS ASSOCIATED ASEPTIC MENINGITIS IN AN IMMUNOCOMPETENT PATIENT - Zhivka Stoykova; Tsvetelina Kostadinova; Radka Argirova (Peytchinski Publishing, 2020)
Background: Varicella zoster virus (VZV) is a widespread herpes virus that causes chickenpox after primary infection. Later the virus remains persistent in the sensory nerve ganglia, and it can be reactivated with the manifestation of herpes zoster most often. But reactivation of VZV can manifest as infection of the CNS (central nervous system) even in an immunocompetent host. The detection of VZV Ab by ELISA and VZV-DNA in cerebrospinal fluid by PCR has improved the laboratory conformation of that condition in an immunocompetent host with discreet exanthema. Materials and Methods: Two serum samples and three CSF samples of a patient with aseptic meningitis were tested by ELISA and PCR. Interpretation: This clinical case demonstrates that VZV may be considered in all cases of aseptic meningitis even in immunocompetent individuals without the typical rash. In cases under VZV associated meningitis suspicion, the first detection marker to be positive is VZV-DNA and later anti-VZV IgG in CSF.